NORMA PERILAKU ADVOKAT DALAM RANGKA PENEGAKAN HUKUM - Edi Krisharyanto (Perspektif, 2007)
The function of Legal Behaviour is to direct, to cancel, to change and to determine violation of any person dealing with law as his/her profession. Advocate Legal Behaviour is the main law system that has been written in advocate regulation and code of ethics, so that every advocate committed to appropriate legal behaviour would uphold the law enforcement.